Presentation secrets of Steve Jobs : how to be insanely great in front of any audience - Gallo, Carmine (McGraw-Hill's AccessEngineering., 2013)
Whether he was introducing the new iPhone or delivering a keynote presentation, Steve Jobs electrified audiences with his style and showmanship. He didn't just convey information in his presentations; he told a story, painted a picture, and shared a vision. Now you can do it too, by learning the specific techniques that made Jobs such a captivating communicator. Using Job's presentations as a blueprint, communication-skills coach Carmine Gallo has mapped out a ready-to-use framework of presentation secrets to help you plan, deliver, and refine the best presentation of your life.